æ±‰è¯å£°è°ƒæŽŒæ¡æƒ…å†µåˆ†æž ä»¥å›½ç«‹åˆä¸10æ ¡ä¸ºä¾‹ - Kusumawardhani, Anissa Dian; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
æ‘˜è¦ï¼šæ±‰è¯å››å£°æœ‰4ä¸ªéŸ³è°ƒï¼Œå³é˜´å¹³ï¼Œé˜³å¹³ï¼Œä¸Šå‡å’ŒåŽ»å£°ã€‚Â  æ±‰è¯å››å£°å…·æœ‰ä¸åŒçš„ç‰¹å¾ä¸Žéš¾ç‚¹ï¼Œå¦‚ï¼šä¸åŒè¯»éŸ³å…·æœ‰ä¸åŒçš„æ„ä¹‰ã€‚ æ¯ä¸ªäººå¦ä¹ æŽŒæ¡ç¨‹åº¦äº¦æœ‰æ‰€ä¸åŒï¼Œå› æ¤ï¼Œç¬”è€…å¯¹å¤ç”¸å›½ç«‹åˆä¸åçš„ å¦ç”Ÿè¿›è¡Œäº†å…³äºŽæ±‰è¯å››å£°æŽŒæ¡æƒ…å†µçš„è°ƒæŸ¥ã€‚æœ¬æ–‡çš„ä¸»è¦ç›®çš„æ˜¯è¯¥æ ¡ å¦ç”Ÿçš„å‘éŸ³éš¾ç‚¹éƒ½æœ‰å“ªäº›å’Œè¯¥æ ¡å¦ç”Ÿå¯¹æ±‰è¯å››å£°çš„æŽŒæ¡æƒ…å†µå¦‚ä½•ã€‚ é€šè¿‡ç ”ç©¶æ–¹æ³•æ˜¯å®šæ€§ç ”ç©¶ä¸Žæè¿°æ–¹æ³•ã€‚ç ”ç©¶è®¾è®¡åŒ…è¿‡ï¼šè§‚å¯Ÿæ³•ï¼Œé—®å·è°ƒæŸ¥ï¼Œå’Œæµ‹è¯•é¢˜ã€‚ç ”ç©¶åŽå¾—åˆ°çš„ç»“è®ºæ˜¯å¦ç”Ÿæœ‰è¯è°ƒå‘éŸ³å›°éš¾ï¼Œå°¤å…¶æ˜¯ç¬¬äºŒå£°ã€‚æœ‰å‡ ä¸ªåŽŸå› å¯¼è‡´äº†å¦ç”Ÿè¯è°ƒå‘éŸ³å›°éš¾ã€‚ç¬¬ä¸€ï¼Œæ¯è¯çš„å½±å“ï¼Œç¬¬äºŒï¼Œä¸“é—¨è®²è§£æ±‰è¯å››å£°çš„æ—¶é—´ä¸è¶³ï¼›ç¬¬ä¸‰ï¼Œå£°è°ƒç›¸ä¼¼ï¼›ç¬¬å››ï¼Œå¦ç”Ÿçš„å¦ä¹ å…´å’Œå¦ä¹ åŠ¨æœºï¼›ç¬¬äº”ï¼Œå¦ç”Ÿæ²¡æœ‰æ±‰è¯åŸºç¡€ï¼›ç¬¬å…ï¼Œæ•™å¸ˆçš„æ•™å¦æ³•ã€‚ å…³é”®è¯ï¼šæ±‰è¯å£°è°ƒ ï¼Œå‘éŸ³éš¾ç‚¹ï¼Œæ±‰è¯å››å£°æƒ…å†µ Abstract: Mandarin Â has 4 tones: yin ping, yang ping, shang sheng and qu sheng. Every Mandarin tones has different characteristics and difficulities, such as the different ways to read and every words has different meanings. The level of every persons in mastering Mandarin tones is different, so the writer did a research about mastering mandarin tones at students of SMP N 10 Pontianak. The main purpose is to find out studentsâ€™ difficulities in mastering mandarin tones and to understand the mastery of mandarin tones on students. The method of this research is qualitative method in form of descriptive method. The study design included: observation, questionnaire, and the test methods. After research what we can get the conclusion is most of the students have the difficulty of speaking the tones, especially at the second tone . Here are some reasons such as: first, students get used to with mother tongue, second Mandarin-studying time is not enough; third , some of tones are similarly; fourth, students learning motivation and interest; fifth, background of learning mandarin; Â and last, the teaching methods. Keywords: mandarin tones, difficulties of mastering tones , condition Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Â Â Â Â of mastering tones